Degradation characteristics of metal/Al2O3/n-InGaAs capacitors - Palumbo, Félix Roberto Mario (2014)
Implementation of new materials in Metal-Oxide-Semiconductor stacks requires capabilities to predict long-time degradation as well as the impact of process changes on degradation processes. In this work, the degradation under constant voltage stress of metal gate/Al2O3/InGaAs stacks is studied for different pre-dielectric deposition treatments. The results show that the degradation, particularly under negative bias, is strongly affected by the oxide-semiconductor surface treatment of the samples. Two contributions (interface states and bulk traps) dominate depending on the stress conditions. Surface treatment with NH4OH shows a better quality of the interface in term of interface states; however, it contributes to generation of positive charge on the dielectric layer.